Science of synthetic turf surfaces: player-surface interactions - Kathryn A. Severn; Paul Fleming; Neil Dixon (2010)
This research project has investigated the mechanical properties and behaviour of third generation synthetic turf surfaces used for football and rugby, with a focus on the traction behaviour produced at the shoe-surface interface. The physical characteristics and mechanical properties of the component materials used in the construction of third generation surfaces were examined. The bulk density of the rubber infill material was found to be a key variable. This was shown to be influenced by compaction and the resulting compression of the rubber infill material under an applied load. Increasing the compactive effort and/or compression under loading increased the bulk density. Shear strength of the rubber infill material was shown to be influenced by bulk density, increasing with a higher bulk density. The composite surface system behaviour of third generation synthetic turf surfaces was investigated. Several surface variables were measured including; shockpad thickness, synthetic turf carpet construction, infill thickness, infill bulk density and infill material type. Shockpad thickness, rubber infill thickness and bulk density were found to influence the impact behaviour, with a thicker rubber layer (shockpad and/or rubber infill layer) reducing the hardness of a surface system. Increasing the bulk density of the rubber infill with compactive effort increased the surface system hardness. Traction behaviour of composite surface systems was explored using three traction test methods to measure both rotational and translational traction. Rubber infill bulk density was shown to be a primary influencing variable from the playing surface variables investigated. Several further traction variables were explored to provide a fuller understanding of the mechanisms involved in the production of traction at the shoe-surface interface including; vertical stress, stud configuration, stud dimension, stud penetration, water and temperature. Vertical stress and stud configuration were found to be primary variables influencing traction development. A traction framework has been developed identifying the factors affecting the production of traction at the shoe-surface interface. It is intended that the traction framework can be used by the sports surface industry, sports governing bodies and academia to aid in the decisions and judgements made during the design, construction and maintenance of these surfaces to obtain desired characteristics and optimise performance and safety.